Komunikasi Antarbudaya di Kalangan Relawan Gubuk Pustaka Ndalung Kecamatan Ajung Kabupaten Jember - Ahmad Nur Hidayatul Ikhwan; Kun Wazis (Icon: Islamic Communication and Contemporary Media Studies, 2022)
Ndalung Ajung Jember Library hut, there are 78 active volunteers and all of them are Muslims. Volunteers come from different cultural backgrounds. Some the volunteers came from college students in Jember who came from different regions. Others from communities such as the pandhalungan culture lover community, wildlife lover community, and others. Thus, intercultural communication emerged among volunteers. The focus of this research 1) How is the process of intercultural communication among the volunteers of Gubuk Pustaka Ndalung Ajung Jember? 2) What are the inhibiting factors for the intercultural communication process among the volunteers of Ndalung Library Gubuk Ajung Jember?. The aims of this study  1)To describe the process of intercultural communication among the volunteers of the Ndalung Library of Ajung Jember Gubuk Pustaka. 2) To describe the inhibiting factors of the intercultural communication process among volunteers of Gubuk Pustaka Ndalung Ajung Jember. The research method used descriptive qualitative with data collection techniques used through observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions or verification. The results showed that 1)Intercultural communication that occurred between the volunteers Gubuk Pustaka Ndalung was well implemented. This is evidenced by the interaction between volunteers with different cultural backgrounds, use of language from the Javanese, Madurese and religious differences. Gubuk Pustaka Ndalung  known Pandhalungan culture, according to volunteers this culture is very unique and interesting so that when they join in it. 2)Volunteer barriers to intercultural communication among volunteers in Gubuk Pustaka Ndalung, Ajung District, Jember Regency.